Computational Simulation-Based Virtual Screening, Synthesis and In Vitro Biological Screening of a “Chalcone Hit” as Anti-Inflammatory and Antidiabetic Agents - Raghuram Krishna*, Sanjay Prahlad Umachigi, Shanmuka Anand Pothana, Pradeep Shivakumar (International Journal of Advanced Science and Technology, 2020)
Abstract The main objective of this proposed project is to identify a “chalcone hit” that has the strength to prevent the catalytic biological function mediated by an inflammatory drug target cyclooxygenase 2 (COX-2) and an antidiabetic drug target dipeptidyl peptidase IV (DPP-IV) target enzymes. The x-ray crystallographic structures (COX-2, PDB ID: 1PXX and DPP-IV, PDB ID: 2ONC) were used in the structure-based virtual screening process, where, a database of bioactive chalcones extracted from PubChem database studied for their in-silico target binding affinity against COX-2 & DPP-IV, the “chalcone hit” specific to the individual targets were conventionally synthesised and characterised using physical and spectral methods. In addition, the “chalcone hit” of a specific target was tested using in vitro bioassay protocols. The compounds (Pub Chem CID 5730821) was identified as virtual hit against COX-2, likewise, the compound (Pub Chem CID 262537) was identified as virtual hit against DPP-IV which was exhibited bioactivity in vitro experiment. Among the database of chalcones, we could have identified and selected the top ranked best fit “chalcone hits” which were synthesised further and evaluated in an in vitro COX-2 & DPP-IV enzyme-based assays on their respective hit compound was found to be having COX-2 & DPP-IV inhibitory potential..